Variations of the Organic Matter Composition in the Sea Surface Microlayer: A Comparison between Open Ocean, Coastal, and Upwelling Sites Off the Peruvian Coast - Zäncker, Birthe; Bracher, Astrid; Röttgers, Rüdiger; Engel, Anja (Frontiers in Microbiology, 2017)
The sea surface microlayer (SML) is the thin boundary layer between the ocean and the atmosphere, making it important for air-sea exchange processes. However, little is known about what controls organic matter composition in the SML. In particular, there are only few studies available on the differences of the SML of various oceanic systems. Here, we compared the organic matter and neuston species composition in the SML and the underlying water (ULW) at 11 stations with varying distance from the coast in the Peruvian upwelling regime, a system with high emissions of climate relevant trace gases, such as N2O and CO2. In the open ocean, organic carbon and amino acids were highly enriched in the SML compared to the ULW. The enrichment decreased at the coastal stations and vanished in the upwelling regime. At the same time, the degradation of organic matter increased from the open ocean to the upwelling stations. This suggests that in the open ocean, upward transport processes or new production of organic matter within the SML are faster than degradation processes. Phytoplankton was generally not enriched in the SML, one group though, the Trichodesmium-like TrL (possibly containing Trichodesmium), were enriched in the open ocean but not in the upwelling region indicating that they find a favorable habitat in the open ocean SML. Our data show that the SML is a distinct habitat; its composition is more similar among different systems than between SML and ULW of a single station. Generally the enrichment of organic matter is assumed to be reduced when encountering low primary production and high wind speeds. However, our study shows the highest OM enrichments in the open ocean which had the lowest primary production and the highest wind speeds.